DESAIN MODEL PEMBELAJARAN BLENDED LEARNING PADA PERKULIAHAN HUBUNGAN INTERNASIONAL - Irwan Irwan; Monica Tiara; Rita Angraini (Universitas Muria Kudus, 2019)
Purpose of this researsch is to describe the design of the blended learning learning model in the course of International Relations in the Department of Social and Political Sciences, Universitas Negeri Padang. Blended Learning is a learning model that combines face-to-face lectures in class with online learning based on technology tools. This research is a qualitative research with descriptive analysis. Data is obtained through literature studies, documentation and asking for the opinions of experts related to the learning model that is appropriately implemented in learning in higher education. The results of this study are in the form of a learning model design with a combination of face-to-face learning with the use of technology in accordance with teaching materials and learning outcomes in the course of International Relations. Thus the pattern of interaction between lecturers and students is not always in the classroom but on various occasions who remain connected using internet technology tools. The blended learning design developed is expected to be coherent with the achievement of International Relations learning that has been compiled while increasing the mastery of technology by students and lecturers.